Is primary tumour resection associated with survival improvement in patients with colorectal cancer and unresectable synchronous metastases? A pooled analysis of individual data from four randomised trials. Issue 2 (January 2015) - Faron, Matthieu; Pignon, Jean-Pierre; Malka, David; Bourredjem, Abderrahmane; Douillard, Jean-Yves; Adenis, Antoine; Elias, Dominique; Bouché, Olivier; Ducreux, Michel
Abstract Objective To evaluate the impact on survival of primary tumour resection in patients with unresectable synchronous metastases from colorectal cancer (CRC). Summary background data Primary tumour resection in this setting remains controversial. Patients and methods We retrieved individual data of 1155 patients with metastatic CRC included in four first-line chemotherapy trials: Fédération Francophone de Cancérologie Digestive (FFCD)-9601, FFCD-2000-05, Actions Concertées dans les cancers COloRectaux et Digestifs (ACCORD)-13, and ML-16987. Patients with unresectable synchronous metastases were eligible for this study. We used univariate and multivariate analyses (Cox models stratified on the trial) to assess the impact of primary tumour resection and other potential prognostic variables on overall survival (OS) (the primary endpoint). Results Amongst the 1155 patients, 810 patients met the inclusion criteria and 59% (n = 478) underwent resection of their primary tumour, prior to trial entry (resection group). Compared to patients in the non-resection group (n = 332 [41%]), those in the resection group were more likely to have a colonic primary, lower baseline carcinoembryonic antigen (CEA) and alkaline phosphatase levels, and normal white-blood-cell count (p < 0.001 each). Primary tumour resection was independently associated to better OS in multivariate analysis (hazard ratio (HR), 0.63 [0.53–0.75]; p < 0.001, with a more favourable impact of resection on OS in case of rectal primary and low CEA level. Primary tumour resection was also independently associated to a better progression-free survival in multivariate analysis (HR, 0.82 [0.70–0.95]; p < 0.001). Conclusion Primary tumour resection was independently associated to a better OS in patients with CRC and unresectable synchronous metastases.